Biphenotypic sinonasal sarcoma with PAX3::MAML3 fusion transforming into high-grade rhabdomyosarcoma: report of an emerging rare phenomenon - Meyer, Anders; Klubíčková, Natálie; Mosaieby, Elaheh; Grossmann, Petr; Kalmykova, Antonina; Koshyk, Olena; Michal, Michael (Virchows Archiv, 2023)
We report a case of a 67-year-old male patient with a sinonasal tumor that showed areas of classic biphenotypic sinonasal sarcoma (BSNS) which in some sections sharply transitioned into high-grade rhabdomyosarcoma. Immunohistochemically, the conventional BSNS parts showed S100 protein, SMA, PAX7, and focal MyoD1 expression, whereas desmin and myogenin were negative. In contrast, the cells in high-grade areas expressed desmin, MyoD1, myogenin, and PAX7, while being negative for S100 protein and SMA. Using the Archer FusionPlex assay, the classical PAX3::MAML3 gene fusion was detected. FISH for PAX3 and MAML3 confirmed a break of these genes in both components. Despite aggressive therapy, the tumor progression resulted in the patient's death. The herein presented case, together with 2 previously published cases of BSNS with high-grade transformation, helps to better understand this novel phenomenon. Although the risk for such transformation appears low, it has important clinical and diagnostic implications which are discussed.
Keywords: Myogenin; High-grade transformation; Rhabdomyosarcoma, Alveolar; Soft Tissue Neoplasms; Rhabdomyosarcoma; rhabdomyosarkom; Humans; lidé středního věku; sarkom; Biphenotypic sinonasal sarcoma; Biomarkers, Tumor; Desmin; PAX3::MAML3; lidé; Immunohistochemistry; Paranasal Sinus Neoplasms; imunohistochemie; nádory měkkých tkání; nádorové biomarkery; Trans-Activators; PAX3 Transcription Factor; S100 Proteins; Sarcoma; transkripční faktor PAX3; Male; Middle Aged; trans-aktivátory; nádory vedlejších dutin nosních; desmin; mužské pohlaví; alveolární rhabdomyosarkom; myogenin; proteiny S100